The effect of Myo-inositol on sperm parameters and pregnancy rate in oligoasthenospermic men treated with IUI: A randomized clinical trial - Ghasemi, Afsane (Int J Reprod Biomed (Yazd), 2019)
BACKGROUND: In about 40% of the couples, the cause of infertility problems is attributed to men because of low sperm production and disturbed motility of sperm. Pieces of evidence show that Myo-inositol has a potential role for the treatment of sperm morphology and male fertility. OBJECTIVE: This study aimed to determine the effect of Myo-inositol on the sperm parameters and fertility rate in patients with oligoasthenospermia treated by intrauterine insemination (IUI). MATERIALS AND METHODS: This study was a randomized clinical trial conducted on 37 patients with oligoasthenospermia treated by IUI during 2016-2017. In this study, the patients were randomly divided into two groups of oligoasthenospermia treated with (Case group) and without Myo-inositol (Control group). The case group received 0.5 ml of Myo-inositol with a concentration of 2 mg/ml and incubated at 37°C incubator for 2 hr, but the control group had no interventions. RESULTS: The results of this study showed that although there was no significant difference in sperm parameters including sperm motility and concentration before processing with Myo-inositol in the case group, but there was a significant increase in sperm motility during the treatment with Myo-inositol. The therapeutic effect of this method was confirmed on induction of pregnancy in 18% of the treated patients, in such a way that was about twice greater than those who did not receive the drug. CONCLUSION: According to the results of this study, the use of Myo-inositol is efficient enough to change sperm parameters to increase the chance of fertility.